2021
DOI: 10.3389/fnagi.2021.654509
|View full text |Cite
|
Sign up to set email alerts
|

Western Diet Induces Impairment of Liver-Brain Axis Accelerating Neuroinflammation and Amyloid Pathology in Alzheimer's Disease

Abstract: Alzheimer's disease (AD) is an aging-dependent, irreversible neurodegenerative disorder and the most common cause of dementia. The prevailing AD hypothesis points to the central role of altered cleavage of amyloid precursor protein (APP) and formation of toxic amyloid-β (Aβ) deposits in the brain. The lack of efficient AD treatments stems from incomplete knowledge on AD causes and environmental risk factors. The role of lifestyle factors, including diet, in neurological diseases is now beginning to attract con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 164 publications
(91 reference statements)
1
42
1
Order By: Relevance
“…Indeed, the Western dietary pattern has been associated with an increased risk of AD, although the underlying mechanisms are not yet completely clear [64]. In experimental studies, the Western diet enhanced brain inflammation and the production of beta-amyloid protein [65]. Furthermore, the Med-Diet, DASH, and MIND diets reduce middle-age CV risk factors that are also risk factors for AD, including vascular disease, hypertension, stroke, diabetes, and obesity [26,[66][67][68][69][70].…”
Section: Meddiet-dash Intervention For Neurodegenerative Delay (Mind Diet)mentioning
confidence: 99%
“…Indeed, the Western dietary pattern has been associated with an increased risk of AD, although the underlying mechanisms are not yet completely clear [64]. In experimental studies, the Western diet enhanced brain inflammation and the production of beta-amyloid protein [65]. Furthermore, the Med-Diet, DASH, and MIND diets reduce middle-age CV risk factors that are also risk factors for AD, including vascular disease, hypertension, stroke, diabetes, and obesity [26,[66][67][68][69][70].…”
Section: Meddiet-dash Intervention For Neurodegenerative Delay (Mind Diet)mentioning
confidence: 99%
“…Nuthikattu et al identified the ESR1 TF as a DEG modulated by the Western diet when comparing the gene expression between female mice groups with a deficiency on low-density lipoprotein receptor in the hippocampus microvessels fed either a control or occidental diet [23]. According to Wiȩckowska-Gacek et al occidental diet may cause metabolic syndromes and diseases due to several factors, including the low consumption of unsaturated FA [24]. The ESR1 TF (nuclear) participates in several DEG-related mechanisms and effects in our study, inhibiting the RXRA TF and the NED4L DEG and activating other genes such as MAPT, ABT, and ACOX2.…”
Section: Discussionmentioning
confidence: 99%
“…The detoxifying function is mainly for hazard product degradation and involves β-amyloid peptides (circulating Aβ). Furthermore, some factors such as insulin resistance hinder the detoxification process, leading to an overall increase in the Aβ level [24]. One of the first steps in AD progression refers to the appearance of pathological Aβ peptides.…”
Section: Discussionmentioning
confidence: 99%
“…The Western diet is linked to an increased risk of AD, although the underlying mechanisms are not fully understood. In mouse models, the Western diet accelerated brain inflammation and the production of beta-amyloid protein [ 18 ]. Additionally, the Medi, DASH, and MIND diets reduce middle-age risk factors for AD, including vascular disease, hypertension, stroke, diabetes, and obesity [ 19 , 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%